FRI0319 Levels of IL-1β and MMP-3 are increased in the synovial fluid from knee osteoarthritis (OA) in patients with concomitant erosive hand OA. (23rd January 2014) - Ramonda, R.; Oliviero, F.; Scanu, A.; Campana, C.; Lorenzin, M.; Modesti, V.; Frallonardo, P.; Punzi, L.
Abstract : Background: Erosive osteoarthritis of the hand (EHOA) is believed to be a subset of HOA targeting interphalangeal (IP) joints and characterised by an abrupt onset, marked pain and functional impairment, inflammatory symptoms and signs, and a worse outcome than non-erosive HOA. Despite these characteristic features, it is still unclear if erosions are found only in predisposed patients or are a consequence of an inflammatory phase occurring in any patient with HOA. Some studies suggest that patients with EHOA share HLA or non-HLA genetic predisposition, in particular associated with a genomic region containing the interleukin (IL)-1β 5810 single nucleotide polymorphism. This would support the hypothesis the IL-1 has a role in the pathogenesis of this severe phenotype of HOA. Objectives: This study was designed to assess the hypothesis that patients with EHOA share a different phenotype from those with non-EHOA. Thus, we investigated if synovial fluid (SF) levels of proinflammatory interleukin (IL)s and metalloproteinase (MMP)-3 from patients with knee OA presenting a concomitant EHOA were different from those with non-EHOA. Methods: In consecutive patients with knee effusions due to OA (ACR criteria), SF was aspirated and subsequently analysed for the presence of crystals and leukocyte (WBC) counts; the remaining SF was stored at -80°C. Patients with crystals of any type and with other concomitant known arthropathies were excluded from the study. Thus, a total of 100 patients were enrolled and underwent hand X-rays which were subsequently examined for the presence of subchondral erosions in the interphalangeal joints. In all SF from patients with erosions of the hand and in 20 consecutive patients without erosions, levels of IL-1β, IL-6, IL-8 and MMP-3 were determined. Statistical analysis was performed with the Mann- Whitney nonparametric test and the Spearman test for correlations. Results: Sixteen out of 100 patients (16%, 11 females, mean age 61.69±7.14), with knee OA had at least one erosion according to X-rays. Serum MMP- 3 levels were higher in EHOA patients with respect to non-EHOA (15.63±3.46 ng/ml vs 10.81±1.71 ng/ml) and the MMP-3 levels were correlated with disease duration (p<0.05; r=0.38) only in the EHOA patients. Significant correlation was found in cytokine levels, particularly in IL-1β (p<0.0001; r=0.91), IL-6 (p<0.05; r=0.53), MMP-3 (p=0.0006; r=0.76) in EHOA patients Conclusions: High levels of cytokines, only in Knee OA patients with EHOA, could suggest that this particular form of OA have a genetic predisposition for the disease and these patients may present a more severe form of general OA Disclosure of Interest: None Declared